Association of Healthy Lifestyle Behaviors and the Risk of Developing Rheumatoid Arthritis Among Women. Issue 2 (11th October 2022) - Hahn, Jill; Malspeis, Susan; Choi, May Y.; Stevens, Emma; Karlson, Elizabeth W.; Lu, Bing; Cui, Jing; Yoshida, Kazuki; Kubzansky, Laura; Sparks, Jeffrey A.; Costenbader, Karen H.
Abstract : Objective: To investigate whether a healthy lifestyle, defined by a healthy lifestyle index score (HLIS), was associated with rheumatoid arthritis (RA) risk, overall and with seropositive/seronegative subtypes. Methods: We analyzed female nurses in the Nurses' Health Study (NHS, 1986–2016) and NHSII (1991–2017). Lifestyle and medical information were collected on biennial questionnaires. Medical records confirmed incident RA and serostatus. The HLIS index includes 5 modifiable components: smoking, alcohol consumption, body mass index, physical activity, and diet. Cox regression, adjusted for confounders, modeled associations between HLIS and incident RA. The population attributable risk estimated the proportion of incident RA preventable if participants adopted ≥4 healthy lifestyle factors. Results: A total of 1, 219 incident RA cases (776 seropositive, 443 seronegative) developed in 4, 467, 751 person‐years. Higher (healthier) HLIS was associated with lower overall RA risk (hazard ratio [HR] 0.86 [95% confidence interval (95% CI) 0.82–0.90]), seropositive RA risk (HR 0.85 [95% CI 0.80–0.91]), and seronegative RA risk (HR 0.87 [95% 0.80–0.94]). Women with 5 healthy lifestyle factors had the lowest risk (HR 0.42 [95% CI 0.22–0.80]). The population attributable risk for adhering to ≥4 lifestyle factors was 34% for RA. Conclusion: In this prospective cohort, healthier lifestyle was associated with a lower RA risk. A substantial proportion of RA may be preventable by a healthy lifestyle.